Incidental Serous Cystadenoma Presenting as a Photopenic Pancreatic Defect on 18F-Fluciclovine PET/CT. (December 2021) - Waltz, Jeffrey; Mercer, Megan K.; Dani, Genta; Rieter, William J.
Abstract : Abstract: 18 F-fluciclovine (Axumin) PET/CT has been widely used for the evaluation of biochemically recurrent prostate cancer following prior treatment. While lymph node and visceral organ metastases typically show increased radiotracer uptake, altered patterns of normal physiologic activity may also provide insight into other disease processes. We present a case of an incidental pancreatic head mass presenting as a photopenic defect on a staging 18 F-fluciclovine PET/CT, which was subsequently confirmed to be a benign serous cystadenoma using multisequence MRI.